تحضير ودراسة الخصائص البنيوية والبصرية لأغشية أكسيد الحديد - بن يامة, مروة; بالطاهر, خلود (Université of eloued جامعة الوادي, 2025)
تمكنا في هذا العمل من تحضير الأغشية رقيقة لأكسيد الحديد الثلاثي 𝐹𝑒2𝑂3 النقي والمطعم بالنيكل Ni بنسب مختلفة )% 2 % . 3.4 .% 8%( باستعمال طريقة الرش بالانحلال الكميائي الحراري عند درجة الحرارة 400℃ بتركيز 0.4𝑚𝑜𝑙𝑙⁄ . الهدف من هذا العمل هو دراسة تثثير تطعيم النيكل على الخصائص الضوئية والبنيوية لشرائح أكسيد الحديد عن طريق إنعراج الأشعة السينية DRX والتحليل الطيفي للأشعة تحت الحمراء، والاشعة فوق البنفسجية والمرئية. حيث أ هًرت النتائا الأشعة السينية تشكل الطور ألفا لأكسيد الحديد وتثخذ المستوي ) 104 ( كاتجا المفضل للنمو وعدم تثثر البنية البلورية بتطعيم بعنصر النيكل. الحجم الحبيبي للشرائح الرقيقة يتراوح بين ) 10.26 - 46.06 ( نانومتر هذ القيم تتعلق بطبيعة تعامل الشبكة البلورية المضيفة مع الذرات الشائبة. قيمة فجوة الطاقة تتراوح بين ) 2.5eV - 2.18 (. كما أ هًرت النتائا التحليل الضوئي أن النفاذية تتناقص بزيادة نسبة التطعيم وشهدت أعلى نسبة لها 86.1% . In this work, we successfully prepared thin films of pure hematite (𝛼−𝐹𝑒2𝑂3) and nickel-doped 𝐹𝑒2𝑂3 with different doping ratios (2%,3,4%, and 8%) using the spray pyrolysis technique at a substrate temperature of 400℃ and a precursor concentration of 0.4𝑚𝑜𝑙𝑙⁄ . The aim of this study was to investigate the effect of nickel doping on the optical and structural properties of iron oxide films. The characterization techniques used included X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), and UV-Visible spectroscopy. The XRD results revealed the formation of the alpha phase (𝛼−𝐹𝑒2𝑂3 ), with the (104) plane as the preferred growth orientation, and showed that the crystal structure was not affected by nickel doping. The grain size of the thin films ranged between 10.26 and 46.06 nm, depending on how the host crystal lattice interacted with the dopant atoms. The optical band gap values varied between 2.5 eV and 2.18 eV. Optical analysis also showed that transmittance decreased with increasing doping ratio, with the highest transmittance recorded
فيزياء الإشعاعات
Keywords: الأغشية الرقيقة أكسيد الحديد، النيكل، الرش بالانحلال الكميائي الحراري; Thin film; iron oxides; nickel; spraying pyrolysis.